=> 2n + 2 chia hết cho n + 2
2n + 4 - 2 chia hết cho n + 2
2 chia hết cho n + 2
n + 2 thuộc Ư(2) = {-2; -1 ; 1 ; 2}
n + 2 = -2 => n = -4
n + 2 = -1 => n = -3
n + 2 = 1 => n = -1
n + 2 = 2 => n = 0
VẬy n thuộc {-4 ; -3 ; -1 ; 0 }
=> 2n + 14 chia hết cho n + 2
2n + 4+ 10 chia hết cho n + 2
10 chia hết cho n + 2
n + 2 thuộc ư(10) = {-10 ; -5 ; -2 ; -1 ; 1;2;5;10}
n + 2 = 1 => n = -1
n + 2 = 2 => n = 0
n + 2 = 5 => n = 3
n + 2 = 10 => n = 8
n + 2 = -10 => n = -12
n + 2 = -5 => n = -7
n + 2 = -2 => n = -4
n + 2 = -1 => n = -3